Implementation of Character Education in Madrasah Students - Moh. Ahsan (Lafadz Jaya Publisher, 2023)
One of the problems that is getting the spotlight and giving rise to public concern today is the emergence of various forms of negative behavior among our students. This study describes the study of the implementation of character education for students in several Indramayu Madrasahs. This research is a qualitative research with descriptive method, because this research aims to get an in-depth picture. Data collection techniques used are observation, interviews, and documentation. The results of this study indicate that in Islam education is not only a process transfer knowledge from teacher to student. Education in Islam is also accompanied by exemplary efforts (Qudwah) of educators in the formation of the character of students. Madrasas as educational institutions must implement character development integrated into subjects, self-development, and Madrasah culture. The learning principles used in the development of national culture and character education strive for students to know and accept cultural values ​​and national character as their own and be responsible for the decisions they make through the stages of recognizing choices, assessing choices, making decisions, and then making a decision. values ​​according to self-confidence.